2015
DOI: 10.1021/acs.est.5b03466
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Disinfection By-Products from Chromatographically Isolated NOM through High-Resolution Mass Spectrometry

Abstract: As levels of natural organic matter (NOM) in surface water rise, the minimization of potentially harmful disinfection by-products (DBPs) becomes increasingly critical. Here, we introduce the advantage that chromatographic prefractionation brings to investigating compositional changes to NOM caused by chlorination. Fractionation reduces complexity, making it easier to observe changes and attribute them to specific components. Under the conditions tested (0.1-0.4 g of Cl to g of C without further additives), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…S3 and S4). When comparing with a previous fractionation study (ESI † Table S5), this description of FT-ICR MS amenable DBPs is consistent with DBPs formed after chlorination of two distinct NOM fractions, 14 one characterized by aromatic compounds with high oxygen content (e.g. polyphenol-like compounds) and the other by compounds with larger carbon-skeletons, typically having more double bonds than oxygen atoms (e.g.…”
Section: Dbp Characteristicssupporting
confidence: 85%
See 3 more Smart Citations
“…S3 and S4). When comparing with a previous fractionation study (ESI † Table S5), this description of FT-ICR MS amenable DBPs is consistent with DBPs formed after chlorination of two distinct NOM fractions, 14 one characterized by aromatic compounds with high oxygen content (e.g. polyphenol-like compounds) and the other by compounds with larger carbon-skeletons, typically having more double bonds than oxygen atoms (e.g.…”
Section: Dbp Characteristicssupporting
confidence: 85%
“…Previous chlorination experiments on isolated NOM fractions prior to FT-ICR MS detection, showed that a fraction constituting oxygenated, unsaturated compounds was the only fraction producing DBPs with multiple chlorine atoms, indicating that these differences also are linked to NOM characteristics. 14,36 When comparing those CHOCl 2 formulae with the CHOCl 2 formulae found in this study, 12 of 65 DBP formulae were common, indicating that part of the CHOCl 2 formulae detected in this study was formed through reaction with similar precursors. 14 The bromide concentration in the raw water at MAL was 0.28 mg L −1 , i.e.…”
Section: Dbp Compositionmentioning
confidence: 59%
See 2 more Smart Citations
“…[18] We also demonstrated that fractionating NOM prior to investigating NOM's interaction with other chemicals (i.e., NaOCl added during water treatment) provides far more definitive results than analyzing bulk NOM. [33] In short, combined chromatographic prefractionation and multiple information-rich analyses have the potential to provide unprecedented structural insight. Structural insight allows more accurate predictions of structure-activity relationships in environmental, pharmacological, toxicological and industrial settings.…”
Section: Introductionmentioning
confidence: 99%